Does Repeated Reading Improve Reading Fluency and Comprehension for Struggling Adolescent Readers? - Still, Kristine Lynn; Flynt, Christine A. (Journal of the American Academy of Special Education Professionals, 2012)
This was a 12-week study that explored the effects of repeated peer readings on struggling adolescent readers. It was a quasi-experimental design with one treatment group and one control group. There were two small group English classes that were consistently using the repeated reading strategy (the treatment group) and students in the co-teach English class who were not using the repeated reading strategy (the control group). The students were not randomly assigned. The pre- and posttests given were the AIMSweb (to measure fluency) and Scholastic Reading Inventory (to measure comprehension). This study investigated the effects of repeated peer reading on reading fluency and comprehension. It also explored the relationship between reading fluency and comprehension. In the area of reading fluency, the results showed that one participant in the treatment group increased and five participants from the control group improved. In the area of reading comprehension, six of the treatment group participants increased and six of the control group participants improved. The participants in the treatment group had larger gains in comprehension than did the control group participants. The data indicated an inconsistent relationship between reading fluency and comprehension.